A Novel Passive Over-Current Trip Device for Seismic Resilience - Lai-Wan Hsu; Jian-Hong Liu; Kun-Long Chen; Pei-Ching Chen; Kuo Lung Lian; Hong-En Chiang; Zhi-Kai Fan; Zhao-Yin Chen; Chung-Liang Cheng; Chi-Feng Chung; Yuan-Ching Tu (IEEE Open Access Journal of Power and Energy)
The seismic resilience has become a critical concern for power systems for high-impact, low-probability disasters such as severe earthquakes. In order to enhance seismic resilience for power systems, a novel protective device, the Passive Over-Current Trip (POCT), has been designed in this paper. In the design, the POCT integrates a fuse and a mechanical switch, able to trigger the breaker to interrupt the circuit to ensure effective protection. The POCT has the trip-free feature as it fulfills its protective function without the need for an electric relay requiring a continuous power supply. The proposed POCT provides an immediate and reliable solution for the protection in high and ultra-high voltage applications. To validate the effectiveness of the proposed POCT, shockproof and tripping tests were conducted. A seismic test waveform from the Fukushima earthquake that occurred on March 11, 2011 was used to test POCT. Under such a severe earthquake, no structural or mechanical damage on the associated components in the POCT was found. Also, the POCT is also in compliance with IEEE 693 standard. Finally, various tripping tests show that the POCT can operate within 18 ms when a fault occurs in a power system, which is much shorter than that of a typical high-voltage fuse.